2014
DOI: 10.3390/s140609776
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Collaborative Ambient Assisted Living Service Description Tool

Abstract: Collaboration among different stakeholders is a key factor in the design of Ambient Assisted Living (AAL) environments and services. Throughout several AAL projects we have found repeated difficulties in this collaboration and have learned lessons by the experience of solving real situations. This paper highlights identified critical items for collaboration among technicians, users, company and institutional stakeholders and proposes as a communication tool for a project steering committee a service descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Although many works have been devoted to proposing new assistive technologies to improve the lives of people with disabilities [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], some studies have found that the abandonment of such technologies is quite high, reaching a rate of up to 30% [ 16 , 17 , 18 , 19 ]. The reasons for abandoning assistive technology are diverse, the most recurrent being that the user does not like the technology; the user is afraid to use the equipment; the user does not believe in the benefit of the device; the technology is not physically fit for the user; the price of the technology is very expensive; the user does not know how to use the equipment correctly; or the user disapproves of the equipment aesthetic factors [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many works have been devoted to proposing new assistive technologies to improve the lives of people with disabilities [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], some studies have found that the abandonment of such technologies is quite high, reaching a rate of up to 30% [ 16 , 17 , 18 , 19 ]. The reasons for abandoning assistive technology are diverse, the most recurrent being that the user does not like the technology; the user is afraid to use the equipment; the user does not believe in the benefit of the device; the technology is not physically fit for the user; the price of the technology is very expensive; the user does not know how to use the equipment correctly; or the user disapproves of the equipment aesthetic factors [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…From clinicians, developers, investors, and governmental authorities up to the users themselves, every stakeholder has different requirements and wants these requirements to be correctly specified so that optimal solution can be achieved. Therefore, there are tools such as the Zaragoza Ambient Assisted Services Description Tool (ZAAS-DT), which aims to assist in the design of AAL systems by helping participants understand the requirements and viewpoints of the different stakeholders [33].…”
Section: Related Workmentioning
confidence: 99%